2012
DOI: 10.5194/acp-12-1629-2012
|View full text |Cite
|
Sign up to set email alerts
|

The isotopic composition of precipitation from a winter storm – a case study with the limited-area model COSMO<sub>iso</sub>

Abstract: Abstract. Stable water isotopes are valuable tracers of the atmospheric water cycle, and potentially provide useful information also on weather-related processes. In order to further explore this potential, the water isotopes H 18 2 O and HDO are incorporated into the limited-area model COSMO. In a first case study, the new COSMO iso model is used for simulating a winter storm event in January 1986 over the eastern United States associated with intense frontal precipitation. The modelled isotope ratios in prec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
126
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(130 citation statements)
references
References 46 publications
4
126
0
Order By: Relevance
“…In the next step, concrete research opportunities should be identified and evaluated. For this purpose, atmospheric models (like COSMOiso, Pfahl et al, 2012) will be essential. Sensitivity tests with the models are needed in order to reveal the links between different moisture processes and distinct {H 2 O,δD} pair distributions and in order to estimate whether the characteristics of the remote sensing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the next step, concrete research opportunities should be identified and evaluated. For this purpose, atmospheric models (like COSMOiso, Pfahl et al, 2012) will be essential. Sensitivity tests with the models are needed in order to reveal the links between different moisture processes and distinct {H 2 O,δD} pair distributions and in order to estimate whether the characteristics of the remote sensing data (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…For the simulation of moisture tracers a secondary water cycle has been introduced in the COSMO model, similar to the implementation of water isotopes by Pfahl et al (2012). As this method is entirely diagnostic, the secondary moisture cycle does not interact with the primary moisture cycle nor affect any other model component.…”
Section: Eulerian Approachmentioning
confidence: 99%
“…These storms carry warm 18 O-enriched vapor to Adak from as south as 29°N (48 h prior) (Figure 2c and Figure S3 in the supporting information). Precipitation has relatively high δ 18 O values, and these are likely amplified by postcondensational exchange with the ambient moisture as it falls to the ground [e.g., Dansgaard, 1964;Pfahl et al, 2012].…”
Section: Processes Controlling δ 18 O Precip On Adak Islandmentioning
confidence: 99%